A Legal Analysis of Consumer Protection Against the Risks Posed by the Online Distribution of Illegal Tabita Cosmetic Products - Sinaga, Maria Adelweys Niken Aprilia; Kurnia, Ida (Jurnal Ilmu Hukum Kyadiren, 2026)
Advances in technology have accelerated the growth of the cosmetics industry; however, these developments are often exploited by businesses to distribute illegal products that fail to meet regulatory and safety standards. This study examines consumer protection mechanisms and the role of the Indonesian Food and Drug Monitoring Agency (BPOM) in responding to the circulation of illegal Tabita-brand cosmetics across digital media platforms. Using normative legal research with statutory and conceptual approaches, this study analyzes both primary and secondary legal materials. The findings indicate that consumer protection efforts are grounded in the Consumer Protection Law (UUPK), the Electronic Information and Transactions Law (UU ITE), BPOM regulations on cosmetics, and relevant e-commerce provisions. Preventive protection is carried out through the provision of accurate product information, while repressive protection consists of administrative, civil, and criminal sanctions. Nevertheless, law enforcement remains hindered by the anonymity of business actors in the digital environment. Although BPOM conducts both pre-market and post-market supervision, the ease of digital distribution continues to facilitate the circulation of illegal products, underscoring the urgent need to strengthen regulations and enhance cross-agency coordination.